Quantum dots as enhancer in photocatalytic hydrogen evolution: A review. (13th April 2017) - Kandi, Debasmita; Martha, Satyabadi; Parida, K.M.
Abstract: Advanced energy conversion processes like photochemical and photoelectrochemical water splitting now a day plays a very important role in challenging the present energy crisis of our world. The successful utilization of this process depends on development of highly efficient, more stable, low cost and outstanding environmental benign semiconductor materials. From recent advancements, it is revealed that quantum dots (QDs) are very outstanding and promising material for the mentioned processes due to their favorable physical and chemical characteristics like high absorption co-efficient, quantum confinement effect, thermal, chemical, mechanical and optical stability, high conductivity and recyclability. In this review article, we have clearly explained the importance of QDs in water splitting along with the general mechanism involved in the process. Following that the enhancement of different materials like metal oxides, layered double hydroxides (LDH), carbonaceous materials (g-C3 N4, benzene and benzene like materials) by QDs have discussed in the field of water splitting. Highlights: This review highlights the importance of QDs in photocatalytic water splitting. QDs as sensitizer and the mechanistic path for H2 evolution are discussed. The advantages of QDs in comparison to bulk materials are explained.